Upaya Meningkatkan Minat dan Prestasi Belajar Sejarah melalui Penerapan Model Pembelajaran Berbasis MasalahSiswa Kelas XI TKJ 1 SMK Negeri 2 Baubau Tahun Pelajaran 2016/2017 - La Ode Zarmin (Jurnal Akademik FKIP Unidayan, 2020)
Problem in this researchare how is the application of problem based learning modelin improving student’s interest and achievement in learning history atgrade XI TKJ 1 SMK Negeri 2 Baubau. This research used classroom action research which is consisted of three cycles. Each cyclesconducted in four stages: planning,action, observation and reflection. The failure in the cycle will becorrected in the next cycle. Subject of the research is grade XIstudents of TKJ 1 SMK Negeri 2 Baubau. The data collection technique which is used in this research is the triangulation resource and method. Analysis data which is used in this method is the analysis of qualitative and quantitative method.After problem based learning model has been applied in SMK Negeri 2 Baubau, there is an improvement of interest to learn until 85% in the third cycle and achievement in every cycle. The improvement achievement in the first cycleoccurred from 49.5 to 75, in the second cyclefrom 53 to 81 and in the third cycle from 60 to 83. Obstacles encountered in the implementation of problem based learning model, among them are the less understanding of student’s concerning problem based learning models at the beginning, students tend to be crowded, and there are students who can not cooperate in a group. The advantages of problem based learning models, among them are students are more active in learning, the ability of students are more honed, the students can train cooperation within the group, to create a spirit of competition between groups, and it is easy for teachers to see the understanding of students of the material.